(untitled) (International Conference on Computers in Education, 2020)
In this paper, we describe our University’s experience based on the institutionalization of industry-recognized certifications as part of the curriculum, specifically for a number of professional computer education courses of students. This is the initial phase of a longitudinal research that we intend to do with the goal of investigating factors that contribute to the effective use of industry certification courses and exams as a supplemental learning infrastructure as it provides formal learning the very relevant practice, resources and data that will inform instructional/curriculum design. We found that academic performance of students in professional courses is predictive of the MTA passing rates when the course content is aligned to that of the certification exam’s topics. With the findings of the data analysis performed in this initial study, we recommend some considerations and guidelines in integrating appropriate certifications to the curricula for higher education using it as a tool for adapting academic learning outcomes to the requirements of the industry.